Low Incidence of Cancer Recorded in the Galapagos Archipelago - Stefano Nicolas Chisesi; Massimo Rugge; Giulia Raffaella Galli; Martina Manni; Veronica Mishell Luzuriaga Delgado; Teodoro Chisesi; Juan Carlos Ruiz; Rina Mariuxi Quinto Briones; Luisa Siculella; Stefano Guzzinati; Manuel Zorzi; Massimo Federico; et al. (Cancer Reports)
ABSTRACT Background Cancer incidence in the Galapagos archipelago is unknown. Aim In 2021, a task force including Ecuadorian and Italian researchers was established to estimate cancer incidence among the 25 244 Galapagos residents. Methods Registration covered all malignancies, including malignant melanoma and non‐melanoma skin cancers; case recording was based on the International Classification of Diseases for Oncology. The data collection involved an active search across all relevant health institutions on the islands and the mainland. Mortality data were obtained from the Ecuador national mortality registry. Results From January 2013 and December 2019, 174 new cancer cases were recorded, including 134 malignancies (M:F = 58:76) and 40 non‐melanoma skin cancers. The mean age at diagnosis was 48 years for males and 56 years for females. Prostate, gastric, and melanocytic malignancies were most incident among males; breast, thyroid, and cervical cancers prevailed in females. The age‐standardized incidence rates (ASR) were 80.39 for males and 99.24 for females with a mortality‐to‐incidence ratio 0.43. These ASRs were significantly lower than those reported in continental Ecuador and other South American countries. Conclusions This pilot cancer registration initiative in the Galapagos record a low incidence of malignancies and requires validation with temporal expansion of cancer registration. The environmental etiology of some of the most common cancers warrants strategic primary and secondary prevention efforts.